The role of lean six sigma in driving sustainable manufacturing practices: an analysis of the relationship between lean six sigma principles, data-driven decision making, and environmental performance - Huang, Jing; Irfan, Muhammad; Fatima, Syeda Saman; Shahid, Rao Muhammad (Frontiers in Environmental Science, 2023)
Introduction: In an increasingly competitive manufacturing sector, companies are adopting innovative approaches, such as the Lean Six Sigma methodology, to enhance their operations, competitiveness, and sustainability. This study explores the effect of Lean Six Sigma methodology and data-driven decision-making on sustainable manufacturing practices. Methods: The study employs thematic analysis to clarify and identify principle nodes and themes, including Six Sigma, quality improvement, management approaches, and front-line worker perspectives. The analysis aims to deepen understanding of Lean Six Sigma principles and their implications for sustainable manufacturing practices. Results: The analysis identifies employee motivation, balanced scorecards, company culture, Customer Relationship Management (CRM), and data-driven decision-making as key drivers of sustainable manufacturing practices. Evidence suggests that implementing Lean Six Sigma methodology, promoting data-driven decision-making, and nurturing a positive company culture enhances environmental performance in the manufacturing industry. Discussion: The findings indicate that Lean Six Sigma, data-driven decision-making, and a positive company culture are effective strategies to enhance sustainability in manufacturing, offering valuable insights for companies seeking to improve sustainability while maintaining competitiveness. This study underlines the potential of Lean Six Sigma as a cornerstone of sustainable manufacturing practices.